1992
DOI: 10.1139/o92-173
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the coordinate expression of muscle genes in a transfected BC3H1 myoblast cell line producing a low level of the adenovirus E1A transforming protein

Abstract: Mouse BC3H1 myoblasts were stably transfected with the adenovirus 5 E1A gene. One clonal line, BC3E7, was found to differ in some important respects from those previously reported for E1A-transformed myoblasts. In contrast to BC3H1 cells which differentiate when confluent in medium containing 0.5% fetal calf serum (FCS), BC3E7 cells failed to elongate and align, to express acetylcholine receptor and creatine kinase, and to down-regulate expression of beta- and gamma-actins and tropomyosin isoform (TM) 1. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…From recent studies on BC3E7 cells, an ElA-transfected BC3H1 line that expresses ElA at a very low level, we concluded that ElA represses myogenic differentiation by repressing transcription of muscle-specific genes directly, rather than as a result of repressing expression of myogenin, a putative myogenic factor in these cells (Mymryk et al, 1992). All of the work discussed here suggests that by binding to p300, ElA proteins are able to repress transcription specifically from cellular genes associated with differentiation.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…From recent studies on BC3E7 cells, an ElA-transfected BC3H1 line that expresses ElA at a very low level, we concluded that ElA represses myogenic differentiation by repressing transcription of muscle-specific genes directly, rather than as a result of repressing expression of myogenin, a putative myogenic factor in these cells (Mymryk et al, 1992). All of the work discussed here suggests that by binding to p300, ElA proteins are able to repress transcription specifically from cellular genes associated with differentiation.…”
Section: Discussionmentioning
confidence: 63%
“…Graham, McMaster University. Transfected cell lines were selected and maintained as described previously (Mymryk et al, 1992 was washed six times in 0.75 ml of the same buffer with centrifugation, and immunoprecipitates were analyzed by electrophoresis on sodium dodecyl sulfate (SDS)-8.5% polyacrylamide gels followed by fluorography.…”
Section: Transfection Of Bc3h1 Cells With Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation